Exploring capital expenditure planning process & tracking in Robi Axiata Limited - Rahi, Md. Sabirul Islam (BRAC University, 2015)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2015.